The Star , 14 Mei 2009 - Jayagandi Jayaraj (Star Publications (Malaysia) Berhad, 2009)
About 30 squatter houses. occupied by foreigners, are the cause of dissatifaction among the locals in Taman Sri Segambut in Kuala Lumpur.